2021
DOI: 10.3390/ijms222212164
|View full text |Cite
|
Sign up to set email alerts
|

Nectar Chemistry or Flower Morphology—What Is More Important for the Reproductive Success of Generalist Orchid Epipactis palustris in Natural and Anthropogenic Populations?

Abstract: The aim of this study was to determine the level of reproductive success (RS) in natural and anthropogenic populations of generalist orchid Epipactis palustris and its dependence on flower structure and nectar composition, i.e., amino acids and sugars. We found that both pollinaria removal and female reproductive success were high and similar in all populations, despite differences in flower traits and nectar chemistry. Flower structures were weakly correlated with parameters of RS. Nectar traits were more imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 107 publications
(207 reference statements)
0
6
0
Order By: Relevance
“…This may indicate that G. repens pollinators need a large amount of AAs, which contrasts with the results of Stabler et al [99]. The most abundant AA in G. repens nectar was Asp, one of the most abundant AAs in the nectar of other orchids [59][60][61][62]. Asp influences pollinator behavior, and is known as a general repellent [101].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…This may indicate that G. repens pollinators need a large amount of AAs, which contrasts with the results of Stabler et al [99]. The most abundant AA in G. repens nectar was Asp, one of the most abundant AAs in the nectar of other orchids [59][60][61][62]. Asp influences pollinator behavior, and is known as a general repellent [101].…”
Section: Discussionmentioning
confidence: 84%
“…The most simple explanation could be the suggestion of Nicolson and Thornburg [38] that nectar sugar composition is determined more by phylogeny than by pollinator preferences. This explanation may explain the low nectar concentration in other orchids [59][60][61][62]. Another possible explanation could be that bumblebees mainly rely on other plants as their main food, with this orchid being a minor component of their diet, especially when its populations are small.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors found that carbon and the ratio of carbon to nitrogen might be the most important factor affecting flower structure and nectar composition. Furthermore, Brzosko et al investigated the impact of the flower structure and nectar chemistry in Epipactis palustris (L.) Crantz, another generalist orchid that is pollinated by over 100 species of pollinators, on reproductive success [ 3 ]. The authors concluded that there are significant differences in nectar chemical properties between natural and anthropogenic populations of E. palustris and pointed out that future study is needed to clarify the most critical factor between pollinator differentiation and soil characteristics.…”
Section: Pollination and Flowering Biologymentioning
confidence: 99%